Strategi Guru Pendidikan Agama Islam (PAI) dalam Pembentukan Karakter Religius Melalui Program Pembiasaan pada Siswa Kelas X di Sekolah Menengah Atas: Islamic Religious Education Teachers' Strategies in Forming Religious Character Through Habituation Programs for Grade X Students in Senior High Schools - Alya Qurratu Aini; Nurul Azizah; Nur Khoirun Nisa; A. Qomarudin (RABBAYANI: Jurnal Pendidikan dan Peradaban Islami, 2025)
The formation of students' religious character currently faces increasingly complex challenges, ranging from issues of globalization, the development of digital technology, and rapid social change that require teachers to have broad insights and have good character. Qualitative research with a case study at SMA Negeri 10 Malang aims to analyze the strategies of Islamic Religious Education teachers in forming the religious character of grade X students. Data collection techniques were carried out through semi-structured interviews and participant observation. The results of the study indicate that the main strategies of Islamic Religious Education teachers in forming religious character are habituation of routine religious activities, teacher role models, an integrative approach in learning and continuous guidance outside of class hours. This study concludes that a comprehensive learning strategy effectively increases students' spiritual awareness and religious behavior, requiring the involvement of all school components, parents, and the environment. The implications of the research include the development of a character development model, increasing the competence of Islamic Religious Education teachers, and creating schools that are conducive to students' spiritual and moral growth